SISTEM INFORMASI PEMETAAN PRAKTEK DOKTER TEMBILAHAN BERBASIS WEB - Nina Megalina Marsalis; Usman Usman (JURNAL PERANGKAT LUNAK, 2023)
Tembilahan City is the center of Indragiri Hilir Regency, located in Riau Province, Indonesia. In the city, technological developments are now more in demand by all groups and also the current internet network speed makes Geographic Information Systems easier to use by the public, including in Doctor's Practice Mapping. Physician practice services are becoming a trend when considering the possibilities felt by society. Usually in one location there are several different specialist doctors, it is said that the number of locations where doctors practice also creates many obstacles that are felt by the community, namely the status of the location of practice or clinic, this setback becomes a solution for the community and also becomes the hope of the community, the decline in this location involves several elements that can be used such as maps, routes, distribution and others. This research aims to make it easier for the community to find and regarding the location of Doctor's Practices in Tembilahan City so that it doesn't take a long time to search. This Web-Based Doctor's Practice Mapping Information System can also display details of the location of practice accurately through digital maps that can help the public to search for practice locations based on the name of the doctor or the name of the location of practice, especially as a promotional medium for doctors who have a place practice in Tembilahan City.